In silico and in vitro antioxidant potential of Thymus serpyllum L. essential oil - Deeksha Salaria; Rajan Rolta; Olatomide A. Fadare; Racheal Y. Fadare; Shikha Guleria; Uma Ranjan Lal; Vikas Kumar (Elsevier, 2023)
Introduction: Thymus serpyllum L. is aromatic plant of Lamiaceae family. Traditionally T. serpyllum is used to cure fever, cold, cough, and mensuration disorders. Present research is focused on to study in silico and invitro antioxidant potential of T. serpyllum essential oil (TEO). Method: Essential oil of T. serpyllum is extracted from areal part by using, hydro-distillation method. In silico antioxidant activity of major phytoconstituents were studied by using autoDock/vina tool. MD simulation was done by using Gromacs. Quantification of thymol in T. serpyllum essential oil was done by GCMS. In vitro antioxidant activity of T. serpyllum essential oil and its active phytoconstituents Thymol was studied by DPPH, FRAP and ABTS method. Results: Molecular docking simulation data revealed that among all the selected phytoconstituents of T. serpyllum essential oil, thymol showed the best binding activity with both the target proteins 1HD2 and 2HCK with docking score -7.9 and -6.9 kcal/mol respectively and follows all the parameters drug likeness and toxicity, it is also stable in 100 ns simulation. Amount of thymol in essential oil was found 248.27524 µg/g. T. serpyllum essential oil showed the good antioxidant activity DPPH (IC50 - 0.755 ± 0.0021%), FRAP (2.78±0.017 µM) and ABTS (2.25 ± 0.0007%). Thymol also showed the good antioxidant activity DPPH (IC50 - 0.68 ± 0.0014%), FRAP (2.25 ± 0.0007 µM) and ABTS (0.15 ± 0.00035%). Conclusion: The current study showed that the essential oil of T. serpyllum and its major phytocompound Thymol has good antioxidant activity and its can be further used as functional food ingredient.